2020
DOI: 10.2196/22324
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Electronic Acupuncture Shoes for Chronic Low Back Pain: Double-Blinded Randomized Controlled Trial

Abstract: Background Chronic low back pain is a common problem and is associated with high costs, including those related to health care and indirect costs due to absence at work or reduced productivity. Previous studies have demonstrated that acupuncture or electroacupuncture can relieve low back pain. Electronic acupuncture shoes (EAS) are a novel device designed in this study. This device combines the properties of acupuncture and transcutaneous electrical nerve stimulation for clinical use. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…These results imply that neuromodulation techniques have additional advantages when compared to a pharmacologic approach in the treatment of chronic pain. EA, a therapeutic means based on acupuncture combined with electrical stimulation, 39 has proven effective in pain relief 40 and multiple organ protection. 41 Parmen et al 42 showed that EA can facilitate an improvement in tissue mechanical stress and enhance the wound healing process without detrimental side effects.…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that neuromodulation techniques have additional advantages when compared to a pharmacologic approach in the treatment of chronic pain. EA, a therapeutic means based on acupuncture combined with electrical stimulation, 39 has proven effective in pain relief 40 and multiple organ protection. 41 Parmen et al 42 showed that EA can facilitate an improvement in tissue mechanical stress and enhance the wound healing process without detrimental side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The pain was assessed at the first visit at the clinic, before and after each EAS treatment, and at 2 weeks after the last treatment. Better results in both analgesic effect and treatment success were obtained in the experimental group, proving that electronic acupuncture shoes could be considered a good alternative treatment for patients with CLBP, who for some reason cannot or do not want to be treated with NSAIDs [18].…”
Section: Acupuncture and Lower Back Pain -Review Of Available Clinica...mentioning
confidence: 89%
“…This device combines acupuncture and transcutaneous electrical nerve stimulation, both of which are already in clinical use. A 6-week treatment protocol indicated that the use of this therapeutic footwear had better treatment success than non-steroidal anti-inflammatory administration ( 33 ).…”
Section: Adaptive/therapeutic Garments For Chronic Painmentioning
confidence: 99%